Bullying in high school students of the state educational institutions of Ugel 07 and level of teacher preparation to address it - Sáenz Chaparro, Sara Mónica (2016)
The phenomenon of bullying is a complex problem that includes not only the students who practice it or suffer it, but also the teachers who interact permanently in the classrooms and in the educational center. This work sought to investigate the presence of bullying in secondary school students and teacher preparation to address it. The research design is comparative descriptive, the sample was 789 students and 40 teachers, all from UGEL 07 state educational centers. The results found indicate a bullying prevalence of 26.4% and 22.5% of teachers who know and use appropriate strategies to address it. Significant differences were found in the prevalence of bullying according to degree of studies; according to gender only in three dimensions: coercion, aggression and intimidation-threats being the highest average in men. No significant differences were found in the approach to bullying by teachers according to gender, age, time of service and academic degree; Finally, no differences were found in the bullying scores of students with trained and under-prepared teachers. These results show that the actions of teachers, in both groups, are limited to face this situation.